A level-set approach to joint image segmentation and registration with application to CT lung imaging - Swierczynski, Piotr; Papiez, Bartomiej W.; Schnabel, Julia A.; Macdonald, Colin (Computerized Medical Imaging and Graphics, 2018)
Automated analysis of structural imaging such as lung Computed Tomography (CT) plays an increasingly important role in medical imaging applications. Despite significant progress in the development of image registration and segmentation methods, lung registration and segmentation remain a challenging task. In this paper, we present a novel image registration and segmentation approach, for which we develop a new mathematical formulation to jointly segment and register three-dimensional lung CT volumes. The new algorithm is based on a level-set formulation, which merges a classic Chan–Vese segmentation with the active dense displacement field estimation. Combining registration with segmentation has two key advantages: it allows to eliminate the problem of initializing surface based segmentation methods, and to incorporate prior knowledge into the registration in a mathematically justified manner, while remaining computationally attractive. We evaluate our framework on a publicly available lung CT data set to demonstrate the properties of the new formulation. The presented results show the improved accuracy for our joint segmentation and registration algorithm when compared to registration and segmentation performed separately.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Atlas-based segmentation; Joint image segmentation and registration; Level-set registration